Research advance on the degradation of antibiotics through advanced oxidation technology using persulfate - YANG Zhiyu; ZHU Ke; XU Zhenhao; ZHANG Xiaodie; YAN Kai* (能源环境保护, 2023)
In recent years, with the improvement of living standards, the production and use of pharmaceutical increased sharply in our country, and pharmaceutical and personal care products (PPCPs) is also growing rapidly, which leads to the continuous existence of emerging contaminants such as pharmaceuticals and PPCPs in the water environment, with antibiotic pharmaceutical contamination being particularly prominent. At present, advanced oxidation technology of persulfate is regarded as a promising water purification technology due to its advantages such as short reaction time, high degradation efficiency and wide application range. This review firstly introduces the use and pollution status of antibiotics in China, and analyzes the source and migration process of antibiotics, then systematically expounds the activation system of persulfate (heat activation, radiation activation, ultrasonic activation and heterogeneous activation of metal/non-metallic catalysts), and discusses the degradation mechanism of advanced oxidation technology of persulfate on antibiotics (radical and non-radical mechanisms). Finally, the existing problems of this research direction are analyzed, and the future development direction is prospected. This review is expected to provide useful information for the practical application of persulfate advanced oxidation process in the degradation of antibiotics.